An experimental and kinetic modeling study of gasoline/lemon peel oil blends for PFI engine. (1st May 2020) - Biswal, Abinash; Kale, Rakesh; Teja, Golakoti Ravi; Banerjee, Sayak; Kolhe, Pankaj; Balusamy, Saravanan
Graphical abstract: Highlights: LPO has higher LHV, similar A/F ratio and comparable octane ratings to that of gasoline. Combustion phasing of LPO blends is the closest match with gasoline. The fuel kinetics of the LPO feedstock leads to enhanced combustion. Brake thermal efficiency of LPO20 and LPO40 are better than gasoline. LPO blends provide an advantage in HC and CO emission reduction with a penalty in NOx emissions. Abstract: The present study is to investigate the suitability of Lemon Peel Oil (LPO) as a partial substitution to a conventional gasoline engine. LPO is a novel, renewable, and sustainable alternative biofuel derived from lemon rinds. LPO is a promising fuel for SI engine operation as its properties such as lower heating value, air/fuel ratio, and octane rating are comparable to gasoline. This study aims to evaluate the combustion, performance, and emission characteristics of two different gasoline-LPO blends in Port Fuel Injection (PFI) engine. For this purpose, two different blends of LPO, 20% and 40% has been prepared with gasoline by volumetric concentration. A comparative analysis of combustion, performance, and emission characteristics are evaluated in a single-cylinder, four-stroke, PFI engine. The obtained results are compared with the baseline fuel gasoline under various engine loads. For statistical understanding, ANOVA with two factors interaction is performed. The experimental results showed that the LPO20 and LPO40 have similar brake thermal efficiency as compared to gasoline. Kinetic modeling and sensitivity studies for LPO and gasoline laminar flames showed that the improved combustion of LPO could be related to its higher laminar flame speeds compared to gasoline at lean and stoichiometric conditions. There is a reduction in HC and CO emission is observed with the addition of LPO in gasoline for each engine loading condition. However, higher NOx emission is noted with an increase in LPO concentration in the blend. Overall, the experimental investigation showed that LPO is a promising alternative renewable source for PFI engines.